(untitled) (Swiss Medical Weekly, 2022)
BACKGROUND: Cerebral Palsy (CP) is a group of permanent disorders of movement and posture that follow injuries to the developing brain. It results in motor dysfunction and a wide variety of comorbidities like epilepsy; pain; speech, hearing and vision disorders; cognitive dysfunction; and eating and digestive difficulties. Central data collection is essential to the study of the epidemiology, clinical presentations, care, and quality of life of patients affected by CP. CP specialists founded the Swiss Cerebral Palsy Registry (Swiss-CP-Reg) in 2017. This paper describes the design, structure, aims and achievements of Swiss-CP-Reg and presents its first results. METHODS: Swiss-CP-Reg records patients of any age diagnosed with CP who are born, are treated, or live in Switzerland. It collects data from medical records and reports, from questionnaires answered by patients and their families, and from data linkage with routine statistics and other registries. The registry contains information on diagnosis, clinical presentation, comorbidities, therapies, personal information, family history, and quality of life. RESULTS: From August 2017 to August 2021, 546 participants (55% male, mean age at registration 8 years [interquartile range IQR: 5–12]), were enrolled in Swiss-CP-Reg. Most had been born at term (56%), were less than two years old at diagnosis (73%, median 18 months, IQR: 9–25), and were diagnosed with spastic CP (76%). Most (59%) live with a mild motor impairment (Gross Motor Function Classification System [GMFCS] level I or II), 12% with a moderate motor impairment (GMFCS level III), and 29% with a severe motor impairment (GMFCS level IV or V). In a subset of 170 participants, we measured intelligence quotient (IQ) and saw lower IQs with increasing GMFCS level. Swiss-CP-Reg has a strong interest in research, with four nested projects running currently, and many more planned. CONCLUSIONS: Swiss-CP-Reg collects and exchanges national data on people living with CP to answer clinically relevant questions. Its structure enables retrospective and prospective data collection and knowledge exchange between experts to optimise and standardise treatment and to improve the health and quality of life of those diagnosed with CP in Switzerland. ClinicalTrials.gov identifier: NCT04992871